What makes a marriage last : 40 celebrated couples share with us the secrets to a happy life - Thomas, Marlo; Donahue, Phil (HarperOne, an imprint of HarperCollinsPublishers, 2020)
"Long-married icons Marlo Thomas and Phil Donahue offer a collection of intimate conversations with famous couples about their long marriages and how they have made their partnerships last. What makes a marriage last? Who doesn't want to know the answer to that question? To unlock this mystery, iconic couple Marlo Thomas and Phil Donahue crisscrossed the country and conducted intimate conversations with forty celebrated couples whose long marriages they've admired -- from award-winning actors, athletes, and newsmakers to writers, comedians, musicians, and a former U.S. president and First Lady. Through these conversations, Marlo and Phil also revealed the rich journey of their own marriage. What Makes a Marriage Last offers practical and heartfelt wisdom for couples of all ages, and a rare glimpse into the lives of husbands and wives we have come to know and love. Marlo and Phil's frequently funny, often touching, and always engaging conversations span the marital landscape -- from that first rush of new love to keeping that precious spark alive, from navigating hard times to celebrating triumphs, from balancing work and play and family to growing better and stronger together. At once intimate, candid, revelatory, hilarious, instructive, and poignant. Featuring interviews with: Alan and Arlene Alda ; Kevin Bacon and Kyra Sedgwick ; President Jimmy and Rosalynn Carter ; James Carville and Mary Matalin ; Deepak and Rita Chopra ; Patricia Cornwell and Staci Gruber ; Bryan Cranston and Robin Dearden ; Billy and Janice Crystal ; Jamie Lee Curtis and Christopher Guest ; Ted Danson and Mary Steenburgen ; Viola Davis and Julius Tennon ; Gloria and Emilio Estefan ; Michael J. Fox and Tracy Pollan ; Chip and Joanna Gaines ; Sanjay and Rebecca Gupta ; Mariska Hargitay and Peter Hermann ; Neil Patrick Harris and David Burtka ; Ron and Cheryl Howard ; Jesse and Jacqueline Jackson ; Elton John and David Furnish ; John and Justine Leguizamo ; LL Cool J and Simone I. Smith ; Melissa McCarthy and Ben Falcone ; John McEnroe and Patty Smyth ; Mehmet and Lisa Oz ; Rodney and Holly Robinson Peete ; Letty Cottin Pogrebin and Bert Pogrebin ; Rob and Michele Reiner ; Kelly Ripa and Mark Consuelos ; Al Roker and Deborah Roberts; Ray and Anna Romano ; Tony Shalhoub and Brooke Adams ; Judges Judy and Jerry Sheindlin ; George Stephanopoulos and Ali Wentworth ; Sting and Trudie Styler ; Capt. Chesley "Sully" and Lorrie Sullenberger ; Lily Tomlin and Jane Wagner ; Judith and Milton Viorst ; Judy Woodruff and Al Hunt ; Bob Woodward and Elsa Walsh." --